2016
DOI: 10.14324/111.444.ijsp.2017.04
|View full text |Cite
|
Sign up to set email alerts
|

More than just a bracelet: the use of material symbolism to communicate love

Abstract: There is growing recognition of the place of love in residential care for children (Smith, 2009). This paper is a critical analysis of a range of existing research on residential child care as well as studies of material culture and of care relationships more broadly. It argues that, despite increasing regulation and surveillance, adults and children find ways to show and feel love in the context of residential care. Whilst love may be regarded as something to be avoided or indeed prohibited in an adult/child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Less attention has been paid to how existing relationships are reinforced through ongoing interactions with objects, and to the ways in which objects can help to construct new relationships. Research conducted in residential care settings for children has found that the gifting of objects can create and reinforce emotional ties between children and adult members of staff (Emond 2016). I suggest that the lack of comparable research in older people's residential settings into how objects can facilitate social interaction, reflects dominant assumptions that older people are predominantly past oriented and have limited capacity to use objects to form new social relationships.…”
Section: Decisions About What We Do With Objects Then For Example Whmentioning
confidence: 98%
“…Less attention has been paid to how existing relationships are reinforced through ongoing interactions with objects, and to the ways in which objects can help to construct new relationships. Research conducted in residential care settings for children has found that the gifting of objects can create and reinforce emotional ties between children and adult members of staff (Emond 2016). I suggest that the lack of comparable research in older people's residential settings into how objects can facilitate social interaction, reflects dominant assumptions that older people are predominantly past oriented and have limited capacity to use objects to form new social relationships.…”
Section: Decisions About What We Do With Objects Then For Example Whmentioning
confidence: 98%
“…Las actividades de la vida diaria, en los recursos residenciales, son oportunidades para trabajar aspectos de interés pedagógico en escenarios de vinculación afectiva reparadora con la figura profesional, situación que supera los tiempos previstos de tutorías (Sala, 2019). Los lazos relacionales, en contextos residenciales, se fraguan en actuaciones prácticas que se dan en la cotidianeidad de los cuidados culturales (Emond, 2016). Los tiempos de intervención directa se ven afectados por la carga laboral de los equipos que se ejecuta en un entorno lleno de dificultades (Fernández-Simo et al, 2020;Lindahl & Bruhn, 2017).…”
Section: Discusión Y Conclusionesunclassified
“…Conventionally, many materials are employed as signifiers of love (Emond, 2016). People frequently use these materials to manifest their love, and such materials are closely related to the feeling of affection.…”
Section: Symbolic Materialsmentioning
confidence: 99%